Managing creativeness in a research laboratory lessons learned from establishing NAMU Lab./EMMI Lab. - Lugmayr, Artur (Bled eCommerce Conference, 2012)
Managing and leading a research laboratory requires many skills, high degree of flexibility, setting visionary goals, ability to cope with institutional and funding agencies policies, among many other needs. However, within the scope of this publication, the focus is on creative research groups, how teams can be motivated, and reviews methods that let creativeness within these laboratories float. This case study builds on the practical experiences of establishing the New Ambient Media Research Lab. (NAMU Lab.) and the Entertainment and Media Management Research Lab. (EMMi Lab.) at the Tampere Univ. of Technology (TUT). Both have been partially been built on the basis of 'Design Thinking' as a method that fosters creativeness in multidisciplinary teams.